Project Based Learning Model on Basic Competencies of Light Vehicle Front Suspension System Maintenance at SMK - Firdaus, Hendi; Anggrainy, Sherlly Dwi; Abdillah, Hamid (Jurnal Ilmiah Profesi Pendidikan, 2023)
Vocational High School (SMK) is an educational institution that offers learning to acquire specific skills. After students graduate from school, they must be able to interact effectively and professionally and have competence. Project-based learning is applied to increase student involvement in order to achieve competence. The approach used in this study is a descriptive qualitative method to describe what PjBL is. Qualitative research aims to understand social phenomena through student involvement in the learning process. Techniques for collecting data include surveys, project assignments, student observations of the learning process to have a positive impact i.e. students become competent. The results of the research were from 10 groups of students, 8 groups were competent, 1 was quite competent, and 1 was very competent. Other research shows how using PjBL in the classroom can help students become more committed.